Sharp Real-Part Theorems A Unified Approach - Kresin, Gershon; Maz'ya, Vladimir (Lecture Notes in Mathematics,, 2007)
This volume contains a coherent point of view on various sharp pointwise inequalities for analytic functions in a disk in terms of the real part of the function on the boundary circle or in the disk itself. Inequalities of this type are frequently used in the theory of entire functions and in the analytic number theory. Rich opportunities are anticipated to extend these inequalities to analytic functions of several complex variables and solutions of partial differential equations.